Numerical homogenization of polymer/clay nanocomposites by the boundary element method - Ptaszny, J.; Fedeliński, P. (Archives of Mechanics, 2011)
The paper deals with the numerical homogenization of polymer/clay nanocomposites by using the boundary element method (BEM). The reinforcement has the form of stacks of parallel clay sheets modelled by effective isotropic particles. Two-dimensional representative volume elements (RVEs), containing randomly distributed parallel rectangular particles, are modelled and five plane-strain elastic constants of the orthotropic composite are analysed: two Young’s moduli, shear modulus and two Poisson’s ratios. The results are compared to experimental data, finite element method (FEM) results, and analytical models as well. The positive-definiteness and symmetry of the apparent compliance matrix are verified. All the comparisons and tests confirm validity of the applied method.